Aromatic Amines Exert Contrasting Effects on the Anticoagulant Effect of Acetaldehyde upon APTT - La'Teese Hall; Sarah J. Murrey; Arthur S. Brecher (Advances in Hematology)
The pharmacological effects of amphetamine, procaine, procainamide, DOPA, isoproterenol, and atenolol upon activated partial thromboplastin time in the absence and presence of acetaldehyde have been investigated. In the absence of acetaldehyde, amphetamine and isoproterenol exhibit a procoagulant effect upon activated partial thromboplastin time, whereas atenolol and procaine display anticoagulant effects upon activated partial thromboplastin time. DOPA and procainamide do not alter activated partial thromboplastin time. Premixtures of procaine with acetaldehyde produce an additive anticoagulant effect on activated partial thromboplastin time, suggesting independent action of these compounds upon clotting factors. Premixtures of amphetamine with acetaldehyde, as well as atenolol with acetaldehyde, generate a detoxication of the anticoagulant effect of acetaldehyde upon activated partial thromboplastin time. A similar statistically significant decrease in activated partial thromboplastin time is seen when procainamide is premixed with acetaldehyde for 20 minutes at room temperature. Premixtures of DOPA and isoproterenol with acetaldehyde do not affect an alteration in activated partial thromboplastin time relative to acetaldehyde alone. Hence, a selective interaction of atenolol, procaine, and amphetamine with acetaldehyde to produce detoxication of the acetaldehyde is suggested, undoubtedly due to the presence of amino, hydroxyl, or amide groups in these drugs.